Precision in practice, save the limb, save the life: Early detection of grade IIA acute limb ischemia and management using catheter-directed thrombolysis - A case report - Niazta, Nisa Amnifolia; Kurnianingsih, Novi; Kurniawan, Dea Arie (Universitas Brawijaya, 2025)
Background: Acute limb ischemia is an emergency condition that causes high morbidity and mortality. Endovascular revascularization in acute limb ischemia showed better in-hospital clinical outcomes than surgical revascularization. Case illustration: A 67-year-old man was referred by internal medicine at the rural area hospital with a diagnosis of acute limb ischemia. He complained of sudden left leg pain and numbness of the left leg 2 days prior to hospital admission. He was a heavy smoker and had a predisposition for atrial fibrillation. He received heparinization at the previous hospital. Upon arriving at Saiful Anwar Hospital, a physical examination showed severe left leg pain and was difficult to move. His left leg was pulseless, paresthesia and poikilothermia. Duplex ultrasound revealed a thrombus in the left popliteal artery with no flow downwards. We diagnosed the patient with Acute Limb Ischemia Rutherford IIA left inferior extremity. We decided to perform catheter-directed thrombolysis with the Alteplase regiment. Post catheter-directed thrombolysis angiography evaluation showed TIMI flow II at the left leg after 24-hour catheter-directed thrombolysis. The patient did not complain of leg pain or numbness anymore. Conclusion: Good outcomes in this patient were obtained through the ability to make correct initial diagnosis, early administration of heparin, and immediate referral to a cardiovascular center that can provide endovascular treatment. Catheter-directed thrombolysis is the right choice for grade IIA acute limb ischemia